2021
DOI: 10.3390/s21103490
|View full text |Cite
|
Sign up to set email alerts
|

Studying Soft Interfaces with Shear Waves: Principles and Applications of the Quartz Crystal Microbalance (QCM)

Abstract: The response of the quartz crystal microbalance (QCM, also: QCM-D for “QCM with Dissipation monitoring”) to loading with a diverse set of samples is reviewed in a consistent frame. After a brief introduction to the advanced QCMs, the governing equation (the small-load approximation) is derived. Planar films and adsorbates are modeled based on the acoustic multilayer formalism. In liquid environments, viscoelastic spectroscopy and high-frequency rheology are possible, even on layers with a thickness in the mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 224 publications
(284 reference statements)
0
79
0
Order By: Relevance
“…The complex frequency shift, Δ f + i Δ Γ , is proportional to the area‐averaged complex amplitude of the stress exerted onto the resonator surface by the sample. The ratio of the shear stress to the transverse velocity is the “load impedance.” [ 23 ] Impedances of this kind have analogies in electricity (in which case the impedance is a voltage‐to‐current ratio rather than a stress‐to‐velocity ratio). As in electricity, there are equivalent circuits available for modeling.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The complex frequency shift, Δ f + i Δ Γ , is proportional to the area‐averaged complex amplitude of the stress exerted onto the resonator surface by the sample. The ratio of the shear stress to the transverse velocity is the “load impedance.” [ 23 ] Impedances of this kind have analogies in electricity (in which case the impedance is a voltage‐to‐current ratio rather than a stress‐to‐velocity ratio). As in electricity, there are equivalent circuits available for modeling.…”
Section: Resultsmentioning
confidence: 99%
“…The advanced QCMs (also termed “QCM‐D” for QCM with dissipation monitoring) report the resonance bandwidth in addition to the resonance frequency and they do so on a number of different overtones. [ 23 ] This added information typically is turned into an estimate of the sample's softness.…”
Section: The Qcm As An Instrument To Detect and Quantify Foulingmentioning
confidence: 99%
See 1 more Smart Citation
“…Last but not least, the transition between regimes III and IV is likely defined by the limited sensing depth of QCM-D. The sensing depth in water (as well as ultrasoft HA films) is on the order of a few 100 nm 69 , 70 which is rather close to the radius of gyration of the largest HA chains ( R g ≈ 75 nm for HA 838 kDa); therefore, even with only moderate chain stretching the HA brush thickness can readily exceed the QCM-D sensing depth. Indeed, we have previously reported brushes made from the largest HA chains to reach thickness values in the range of hundreds of nanometres and to be very soft, explaining why they can give rise to very modest negative normalised frequency shifts (in the range of few Hz; see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The QCM sensor based on AT-cut quartz crystals can be used in liquid medium [2,3] and passive interrogation at resonance is currently the basic method [4][5][6]. Reviews on the QCM electronic interfaces can be found in [7][8][9]. QCM sensors are now widely used as biosensors [10][11][12] and have been combined with scanning force microscopy, optical reflectometry, electrochemistry, and other interface analysis tools.…”
Section: Introductionmentioning
confidence: 99%